FORMASI DAN NEGOSIASI IDEOLOGI DALAM NASKAH HIKAYAT PRANG GOMPENI ANALISIS HEGEMONI GRAMSCI - Zaki Achmad (An-Nahdah Al-'Arabiyah, 2023)
This study aims to describe the formation and negotiation of ideology in the text of Hikayat Prang Gompeni by Abdul Karim by using Gramsci's Hegemony analysis. Hikayat Prang Gompeni (HPG) was written in three langauages; Malay, Acehnese, and some words derived from Arabic. The HPG manuscript is written in prose. This manuscript tells about the danger of if the Dutch conquered the land of Aceh and calls for war against the infidels in order to uphold Islam. This research uses the descriptive method that the research data is classified, analyzed and concluded. The result of this study indicates that there are six ideological formations found in HPG, those are apathy, edemonism, colonialism, conservatism, humanism, and theism which the negotiator ideologies are humanism and edemonism.